ANALYSIS OF TRANSPARENCY, ACCOUNTABILITY, COMMUNITY PARTICIPATION, AND ACCOUNTING INFORMATION SYSTEMS IN VILLAGE FUND MANAGEMENT - Ummah, Erina Fazia Rotul; Junjunan, Mochammad Ilyas; Nufaisa, Nufaisa (IPSAR (International Public Sector Accounting Review), 2024)
The village government must be able to manage village funds properly because the better the management of village funds, the higher the level of transparency, accountability in the management of village funds. The purpose of this study was to determine the effect of transparency, accountability, community participation and accounting information systems on the management of village funds. The sample of this study was the village head, village secretary, village treasurer, head of service and general affairs, government affairs, welfare affairs, hamlet head, BPD chairman and LPMD chairman with a total of 213 respondents spread across 24 villages in the temple sub-district who participated in the study. The research analysis technique uses multiple linear regression with a probability value of 5% using t-table testing using SPSS 26 software. The results obtained show that accountability, community participation and accounting information systems are able to influence the management of village funds. While transparency is not able to significantly affect the management of village funds.